Gallic acid inhibits osteoclastogenesis and prevents ovariectomy-induced bone loss - Zhang, Peng; Ye, Jiekai; Dai, Jiale; Wang, Ying; Chen, Genjun; Hu, Jinping; Hu, Qimiao; Fei, Jun (Frontiers in Endocrinology, 2022)
Osteoporosis is a common metabolic bone disease with a rapidly increasing prevalence, characterized by massive bone loss because of excessive osteoclast formation. Gallic acid (GA), a phenolic acid isolated from Cornus officinalis, has anti-inflammatory and anti-oxidant effects, but its effect on osteoclast formation has not been confirmed. In our study, we demonstrated that GA significantly inhibited RANKL‐induced osteoclast formation and function of osteoclast in bone marrow monocytes (BMMs) and RAW264.7 cells in a dose-dependent manner without cytotoxicity. For molecular mechanisms, GA repressed osteoclastogenesis by blocking Akt, ERK, and JNK pathways, and suppressed osteoclastogenesis-related marker expression, including nuclear factor of the activated T-cell cytoplasmic 1 (NFATc1), c‐Fos, and cathepsin K (CTSK). In addition, we further assessed the effect of GA in an ovariectomized mouse model, which indicated that GA has a notable effect on preventing bone loss. In conclusion, GA exerts notable effects in inhibiting osteoclastogenesis and preventing ovariectomy-induced bone loss, suggesting that GA is a potential agent in osteoporosis treatment.